Effectiveness of Pippalyadi Ointment in Management of Arsha (Haemorrhoids) - Suraj P Rathod; Kiran Khandare (Institute of Medico-legal Publications Pvt Ltd, 2021)
Arsha is a common anorectal disease so associated with bleeding per anum . It can be compared toHaemorrhoids accoding to modern science. Haemorrhoids are dilated veins in the anal canal. Through allthe modern modalities of treatment in haemorrhoids are universally accepted but all have some or otherlimitations. In Ayurveda various measures have been mentioned for the management of Abhyantar Arsha ,among which lepa karma is one of them . Various study have been done on the application of various lepaso prepared have been conducted depending upon the sign and symptoms. Objective- This study was carriedout to find the effectiveness of Pippalyadi ointment in Ptients of Arsha .Materials and Methods- Here thepatient of Arsha were selected as per criteria and Pipplyadi ointment was advised for 15 days twice a dayas local application.